2014
DOI: 10.1681/asn.2013070810
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Targeting or Pharmacologic Inhibition of NADPH Oxidase Nox4 Provides Renoprotection in Long-Term Diabetic Nephropathy

Abstract: Diabetic nephropathy may occur, in part, as a result of intrarenal oxidative stress. NADPH oxidases comprise the only known dedicated reactive oxygen species (ROS)-forming enzyme family. In the rodent kidney, three isoforms of the catalytic subunit of NADPH oxidase are expressed (Nox1, Nox2, and Nox4). Here we show that Nox4 is the main source of renal ROS in a mouse model of diabetic nephropathy induced by streptozotocin administration in ApoE 2/2 mice. Deletion of Nox4, but not of Nox1, resulted in renal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
333
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(361 citation statements)
references
References 62 publications
19
333
3
2
Order By: Relevance
“…However, results obtained with whole body Nox4 knock-out mice are controversial or more complex. One study found that Nox4 deletion indeed mitigated the progression of DKD on the apoE Ϫ/Ϫ background (29). However, Babelova et al (35) using four chronic kidney injury models detected no protective effect of Nox4 deletion; in fact, they reported slight deterioration of obstructive nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, results obtained with whole body Nox4 knock-out mice are controversial or more complex. One study found that Nox4 deletion indeed mitigated the progression of DKD on the apoE Ϫ/Ϫ background (29). However, Babelova et al (35) using four chronic kidney injury models detected no protective effect of Nox4 deletion; in fact, they reported slight deterioration of obstructive nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that Nox4 is up-regulated during and is required for fibroblast-myofibroblast transition in vitro (19,(21)(22)(23). Moreover, Nox4 down-regulation by siRNA or antisense oligonucleotides proved to be protective in a lung fibrosis model (22) and reduced matrix deposition in diabetic kidney disease (DKD) (27), whereas new Nox1/4-selective pharmacological inhibitors exerted potent kidney-protective and antifibrotic effects in DKD models (28,29). All these findings suggest that Nox4 protein levels rise under fibrogenic (predominantly diabetic) conditions, and this contributes to the ensuing nephropathy and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In metabolically compromised animals, oxidant stress is thought to be an important link between glucose disturbances and impaired function of the kidney. Several reports have described a causal role for NOX4 in renal dysfunction that can lead to hypertension 50, 51. In salt‐sensitive rats, urinary hydrogen peroxide has been shown to be elevated with increased renal perfusion pressure, and deletion of renal NOX4 attenuates hypertension 52, 53, 54.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism leading to enhanced NOX activity includes hyperglycaemia‐driven formation of intermediate Amadori products which are oxidised to form AGEs that activate RAGE and stimulate NOX to produce ROS 2. A clear role for elevated NOX1 activity has been shown in the promotion of diabetes‐associated atherosclerosis,9 whilst NOX4 appears critical in driving diabetic nephropathy 10…”
Section: Reactive Oxygen Species and Oxidative Stressmentioning
confidence: 99%